STUDI TENTANG PERILAKU OPERATOR DALAM KESIAPSIAGAAN PENANGGULANGAN BAHAYA KEBAKARAN DI PT. X SURALAYA - Meli Azrini; Hanifa Maher Denny; Laksmono Widagdo (Jurnal Kesehatan Masyarakat (Undip), 2017)
According to World Fire Statistic Report, there are 500 thousands deaths all over the world related to work. One of caused by fire. Fire is an uncontrolled flame that means beyond the capability and human wish. The background of this study was the incidence of fires in PT. X Suralaya, seeing a potential fire hazard while working as an operator and firefighters at the same time. The purpose of this study was to analyze the behaviour of operator against fire prevention preparedness in PT. X Suralaya. This study is a quantitative study with cross sectional approach. The samples used on this research is 76 workers. Data analysis that used on this study is univariate analysis and bivariate analysis with Chi-square test. Bivariate analysis showed that there was no correlation between knowledge with behavior of operator (p-value 0.117), there was no correlation between the availability of firefighting facilities with behavior of operator (p-value 0.221), there was no correlation between regulation with behavior of operator (p-value 0,759), and there was no correlation between supervision with behavior of operator (p-value 0,506). The conclusion of this study is there was no correlation among the variables. Researcher also suggest the company should provide firefighting training regularly for each operator, optimazation of sanction and another researcher use the theory to analyze the behavior of other behaviors.